Enabling the powerful? Participatory action research with local policymakers and professionals for physical activity promotion with women in difficult life situations - Frahsa, Annika; Rütten, Alfred; Röger, Ulrike; Abu-Omar, Karim; Schow, Diana (Health promotion international, 2012)
Enabling is a concept central to health promotion. It is perceived as a mechanism that can help people gain control over determinants of health. Little is known, however, about enabling among policy-makers and professionals. This case study investigates enabling among policy-makers and professionals who engaged in a specific participatory approach, cooperative planning. We define 'enabling' as creating action situations that allow policy-makers and professionals to (i) build individual capacities for health promotion and to (ii) apply these capacities to concrete organizational and political action at the institutional level. This case study followed policy-makers and professionals as they participated in a local physical activity promotion action research project in Germany. We conducted a secondary analysis of qualitative data gathered in that project (2005-2011). Methods included participant observation, document analysis, focus groups and qualitative interviews. All data were revisited for the case study and analyzed using qualitative content analysis. Findings include examples of enabling among policy-makers and professionals related to the cooperative planning process. Individual capacities were developed in perceived project roles, interactions with target groups and decision-making procedures. Findings also demonstrated municipal policy changes. Access to physical activity infrastructures improved, and an intersectoral job position was funded to support physical activity promotion among target group participants. Findings were analyzed using a model that links cooperative planning with a framework on policy change from a political science perspective. We conclude that cooperative planning might be a pathway to negotiated agreements that foster systematic enabling and health-promoting policy change.
Keywords: community-based participatory research; health-promoting policies; physical activity; policy and implementation